The Risks of (Anti-)Muslim Radicalism : Charlie Hebdo, Islamic Minorities and Political Violence in Central Europe - Daniel, Jan (Prague, Czech Republic Institute of International Relations (IIR), 2015)
This paper discusses the increase in anti-Islamic discourse and movements in Europe following the January 2015 terrorist attacks against the French satirical magazine "Charlie Hebdo". The author contends that although the threat to Muslims posed by the discourse and movements is relatively low, governments should still respond to the issue through public engagement, providing security for minority populations and refraining from framing them as a threat to the security of the majority.
Keywords: Islamismo; Radicalismo; Europa Central